ANALISIS RUANG TUNGGU / BOARDING LOUNGE TERHADAP PENINGKATAN JUMLAH PENUMPANG DI BANDAR UDARA EL TARI KUPANG - Yuke Sri Rizki; Yati Nurhayati (Jurnal Ilmu dan Budaya, 2016)
The airport is an air transport infrastructures that must be equipped with a variety of facilities, equipment and services in accordance with applicable regulations. One of the facilities available at the land side is the lounge / boarding lounge to accommodate passengers who are leaving / boarding. Passengers at the airport El Tari Kupang each year continues to increase so that the need to adjust the waiting room as needed. The methodology in this study was descriptive qualitative and forecasting. The results of this study stated that the waiting room at the airport El Tari Kupang should be expanded to waiting passengers feel comfortable flying hours.